(untitled) (Nepalese Veterinary Journal, 2023)
More than 50% of the households of Gandaki province have been rearing buffaloes. Whereas in mid hills 1-2 number of buffalo is present in most houses which are reared for sustainable purpose. A cross sectional study was carried out for a year in the mid hills of Gandaki province selecting 20 farms from four locations; Parbat, Nagi ramche, Tarakhola and Lwang ghalel, Kaski. Similarly, for a year a buffalo farm of Directorate of Agricultural Research, Gandaki was also studied. The purpose of this study was to determine the feeding system of buffalo in midhills and DoAR farm and compare the milk production. The milk production by the indigenous buffalo of local farms (3.3liters/d) was significantly higher than that of DoAR farms(2.9 liters/d) despite of feeding balanced concentrate ration daily. The raulo and khar combination was the main source of roughages whereas maize, barley and millet flour were the common source of concentrate for the indigenous buffalo in mid hills of Gandaki province.